EMOTIONAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE TO INCREASE JOB SATISFACTION IN EMPLOYEES PT PELABUHAN INDONESIA III SURABAYA (PERSERO) TANJUNG PERAK SURABAYA BRANCH - Indriana Kristiawati; Juli Prastyorini; Moch Fariqul Fiqkri Fachrudin (LPPM of NAROTAMA UNIVERSITY, 2023)
This study aims to find out and analyze the influence of Emotional Intelligence and Spiritual Intelligence on Job Satisfaction of PT. Pelindo III (Persero) Tanjung Perak Surabaya branch. This research is quantitative research. Subjek this research is an employee of PT. Pelabuhan Indonesia III (Persero) Tanjung Perak Surabaya branch using a sample of 166 employees. Data collection using questionnaires and interviews, the sampling technique is simple random sampling. Analytical techniques a data was performed using multiple linear regression analysis. Based on the results of hypothesis testing shows that first There is an influence of emotional intelligence on job satisfaction; secondly There is an influence of spiritual intelligence on job satisfaction.